1991
DOI: 10.1016/s0006-3495(91)82120-8
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated and calcium-gated calcium release during depolarization of skeletal muscle fibers

Abstract: The role of elevated intracellular calcium concentration ([Ca2+]) in activating calcium release from the sarcoplasmic reticulum (SR) was studied in skeletal muscle fibers microinjected with strong calcium buffers. After the injection of 3.8 +/- 0.5 mM (mean +/- S.E. of mean, n = 16) BAPTA (1,2-bis[o-aminophenoxy]ethane- N,N,N',N'-tetraacetic acid) or 2.2-2.8 mM fura-2 the normal increase in [Ca2+] during a depolarizing pulse was virtually eliminated. Even though calcium was released from the SR the kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
126
5

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(145 citation statements)
references
References 36 publications
14
126
5
Order By: Relevance
“…The present results together with the recent work of Jacquemond et al (1991) are evidence of a calcium-induced mechanism contributing to physiological calcium release. This, together with the effects of released calcium on the voltage sensor, either causing or modifying the charge movement component Qy Jong, Pape & Chandler, 1992), brings to two the number of positive feedback processes apparently at work in the control of calcium release.…”
Section: Tetracaine Effects On Charge Movementsupporting
confidence: 82%
See 1 more Smart Citation
“…The present results together with the recent work of Jacquemond et al (1991) are evidence of a calcium-induced mechanism contributing to physiological calcium release. This, together with the effects of released calcium on the voltage sensor, either causing or modifying the charge movement component Qy Jong, Pape & Chandler, 1992), brings to two the number of positive feedback processes apparently at work in the control of calcium release.…”
Section: Tetracaine Effects On Charge Movementsupporting
confidence: 82%
“…The pharmacology of this process observed in skinned fibres, isolated triads and reconstituted channels, argues strongly in this direction. Most importantly, Jacquemond, Csernoch, Klein & Schneider (1991) showed that intracellular injection of the fast calcium buffer bis(O-aminophenoxy)ethane-NNN',N'-tetraacetic acid (BAPTA) in frog cut fibres abolishes the peak of calcium release and spares the noninactivating component. The effects of BAPTA are remarkably similar to those of tetracaine reported in this paper and both sets of experiments paint a consistent picture of two release processes, separately controlled by voltage and Ca2 .…”
Section: Two Distinct Pathways Of Calcium Releasementioning
confidence: 99%
“…Our laboratory previously showed that partial depolarization of MHN fibers with KCl increased their [Ca 2ϩ ] i and resulted in increased caffeine response (27). BAPTA is a high-affinity Ca 2ϩ chelator (46, 47) that has been used in several previous studies to reduce [Ca] i in adult skeletal muscle fibers (3,19). As an intracellular Ca 2ϩ buffer, BAPTA has several important advantages over other Ca 2ϩ chelators, because it is practically insensitive to intracellular pH changes, has a greater selectivity for Ca 2ϩ over Mg 2ϩ , is faster than EDTA and EGTA at taking up and releasing Ca 2ϩ , and its dissociation constant is 110 nM (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the early peak of Ca 2ϩ release during voltage-clamp depolarization is composed mainly of CICR, whereas the later quasi-steady level is the result of direct DHPR activation has been repeatedly considered since an early study by Jacquemond et al (112), who reported that Ca buffer specifically inhibits the early peak. Shirokova et al (231) has found that amphibian skeletal muscles, which have equal amounts of RyR␤ and RyR␣, show a much more prominent early peak than do mammalian muscles, which have only a small amount of RyR3, and suggested that Ca 2ϩ released from DHPR-activated RyR␣ channels may activate the CICR of RyR␤ to cause the more-prominent early peak in amphibian muscles (231).…”
Section: B Early Peak Of Voltage-activated Ca 2؉ Release and Cicrmentioning
confidence: 99%